Robo2 and Gen1 Coregulate Ureteric Budding by Activating the MAPK/ERK Signaling Pathway in Mice - Li, Yaxin; Yu, Minghui; Tan, Lihong; Xue, Shanshan; Du, Xuanjin; Wu, Xiaohui; Xu, Hong; Shen, Qian (Frontiers in Medicine, 2022)
Congenital anomalies of the kidney and urinary tract (CAKUT) are some of the most common developmental defects and have a complicated etiology, indicating an interaction of (epi-)genetic and environmental factors. Single gene mutations and copy number variations (CNVs) do not explain most cases of CAKUT, and simultaneous contributions of more than one gene (di-, oligo-, or polygenic effects; i.e., complex genetics) may lead to the pathogenesis of CAKUT. Robo2 plays a key role in regulating ureteric bud (UB) formation in the embryo, with mutations leading to supernumerary kidneys. Gen1 is a candidate gene associated with CAKUT because of its important role in early metanephric development in mice. We established a mouse model with double disruption of Robo2 and Gen1 using a piggyBac transposon and found that double gene mutation led to significantly increased CAKUT phenotypes in Robo2PB/+Gen1PB/+ mouse offspring, especially a duplicated collecting system. Increased ectopic UB formation was observed in the Robo2PB/+Gen1PB/+ mice during the embryonic period. Robo2 and Gen1 exert synergistic effects on mouse kidney development, promoting cell proliferation by activating the GDNF/RET pathway and downstream MAPK/ERK signaling. Our findings provide a disease model for CAKUT as an oligogenic disorder.